2018
DOI: 10.1007/s11748-018-0949-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early tracheostomy on clinical outcomes in critically ill lung transplant recipients

Abstract: Early tracheostomy following lung transplantation decreased both intensive care and hospital stay, due to improved postoperative recovery, even in patients with poor preoperative conditions. Furthermore, length of hospital stay in patients with early tracheostomy was similar to that of patients without tracheostomy after lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…21,22 The potential etiology of voice and swallowing complications in this patient population is poorly understood and has received little attention in the literature. Cardiothoracic transplant surgery and the post-operative course are inherently complex and can involve (1) compromised respiratory function, (2) prolonged intubation, [23][24][25][26] (3) damage to the recurrent laryngeal nerve (RLN), 10,14,27 (4) intensive care unit acquired weakness, 28 (5) alterations to neurological status 9,28 and (6) chronic gastro-oesophageal reflux. [29][30][31] All these factors are known to have a direct association with swallowing and voice dysfunction.…”
mentioning
confidence: 99%
“…21,22 The potential etiology of voice and swallowing complications in this patient population is poorly understood and has received little attention in the literature. Cardiothoracic transplant surgery and the post-operative course are inherently complex and can involve (1) compromised respiratory function, (2) prolonged intubation, [23][24][25][26] (3) damage to the recurrent laryngeal nerve (RLN), 10,14,27 (4) intensive care unit acquired weakness, 28 (5) alterations to neurological status 9,28 and (6) chronic gastro-oesophageal reflux. [29][30][31] All these factors are known to have a direct association with swallowing and voice dysfunction.…”
mentioning
confidence: 99%
“…Although these studies did not stratify patients based on tracheostomy timing or technique, these results suggest that patient comorbidities may be one of the more consistent prognosticators for tracheostomy patients, especially given that tracheostomy patients are likely to be in critically ill conditions caused by a wide array of disease processes. [35][36][37] Interestingly, unknown partner status (e.g., not knowing whether a patient is single, married, divorced) was associated with decreased survival. Several studies have demonstrated an association between unpartnered status (single, divorced, separated, widowed) and negative health outcomes-and similarly an association between partnered status (married, significant other) and improved health outcomes-in a variety of patient populations with diverse underlying disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…Extubation criteria include hemodynamic stability, ability to protect airway, FiO 2 <50%, PEEP of 5 cm H 2 O, Nitric Oxide (NO) <10 ppm, respiratory rate <20/min and minute ventilation <10 mL/kg. For patients who fail to progress, early tracheostomy will facilitate weaning of sedation, pulmonary toilet and ventilator weaning (6).…”
Section: Ventilator Managementmentioning
confidence: 99%